Attempt of Clarifying Some Concepts on Labor Economics - Hambardzumyan, Anahit (Bulletin of Yerevan University G: Economics, 2013)
In this article we considered some concepts of labor economics and tried to comment on their conceptual correct use. On the basis of the international norms and treatments existing in economic literature, need of the correct application of considered concepts of labor economics is proved.